Adult acclimation to combined temperature and pH stressors significantly enhances reproductive outcomes compared to short‐term exposures. (9th December 2014) - Suckling, Coleen C.; Clark, Melody S.; Richard, Joelle; Morley, Simon A.; Thorne, Michael A. S.; Harper, Elizabeth M.; Peck, Lloyd S.
Summary: This study examined the effects of long‐term culture under altered conditions on the Antarctic sea urchin, Sterechinus neumayeri . Sterechinus neumayeri was cultured under the combined environmental stressors of lowered pH (−0·3 and −0·5 pH units) and increased temperature (+2 °C) for 2 years. This time‐scale covered two full reproductive cycles in this species and analyses included studies on both adult metabolism and larval development. Adults took at least 6–8 months to acclimate to the altered conditions, but beyond this, there was no detectable effect of temperature or pH. Animals were spawned after 6 and 17 months exposure to altered conditions, with markedly different outcomes. At 6 months, the percentage hatching and larval survival rates were greatest in the animals kept at 0 °C under current pH conditions, whilst those under lowered pH and +2 °C performed significantly less well. After 17 months, performance was not significantly different across treatments, including controls. However, under the altered conditions urchins produced larger eggs compared with control animals. These data show that under long‐term culture adult S. neumayeri appear to acclimate their metabolic and reproductive physiology to the combined stressors of altered pH and increased temperature, with relatively little measureable effect. They also emphasize the importance of long‐term studies in evaluating effects of altered pH, particularly in slow developing marine species with long gonad maturation times, as the effects of altered conditions cannot be accurately evaluated unless gonads have fully matured under the new conditions. Abstract : This paper shows that acclimation to altered pH takes up to 8 months in Antarctic sea urchins and also that gonads matured for their full development time (2 years) in altered pH significantly enhances reproductive outcomes compared to short term exposures.